PENYELESAIAN SISTEM PEMBENTUKAN SEL PADA HYDRA MENGGUNAKAN METODE BEDA HINGGA SKEMA EKSPLISIT - Sambono, Y.; Leleury, Zeth Arthur; Tomasouw, Berny Pebo; Rahakbauw, Dorteus L. (PATTIMURA UNIVERSITY, 2020)
Mathematical models that describes the pattern of cell formation in hydra are expressed in a system of equations known as the Meinhardt model. This model is a continuous model in the form of diffusion equations. Thus, one of the studies which can be applied to Meinhardt equation is discretization. The finite difference model is a numerical method that can describe the discrete form of a continuous differential form. The method used in this study is finite different methods implementing explicit scheme. The advantage of the explicit scheme is easier to use for solving non-linear partial differential equations. This method used finite forward difference for derivatives of ð‘¡ and finite centre difference for derivatives of ð‘¥ at theactivator ð‘Ž(ð‘¥, ð‘¡) and inhibitor ð‘(ð‘¥, ð‘¡). The Steps conducted by analyzing Meinhardt equation andcontinued with discretization such that earn the solution of system cell formation in hydra. According to the research its found that the activator cell population graphic have cell growth disposed ascend by the unit time, be different with the inhibitor cell population disposed descend of cell growth by the unit time.